Care : reflections on who we are - May, Todd, 1955- (Philosophy: The New Basics, 2023)
Caring is a central aspect of our being. It anchors us to the world and to one another. And yet, understanding what caring is and how it operates in our lives is a challenge. This fascinating book meets that challenge, by canvassing various approaches to care and offering an overview of the key role it plays in our lives.